Analisis Wacana Kritis Norman Fairclough Dalam Iklan Teh Pucuk Harum - Kasvita, Anzza Fellda; Dalimunthe, Syairal Fahmi; Lubis, Malan (Jurnal Ilmiah Wahana Pendidikan, 2026)
Critical discourse analysis is an interdisciplinary approach that examines the relationship between language, text, and social context. Advertisements can be used to convey information, influence audiences, and promote products and services. This research is explained using Critical Discourse Analysis (CDA) which uses Norman Fairclough's theory that views discourse/text (advertising) as consisting of text, discourse practices, and sociocultural practices. The research method used is qualitative. The purpose of this research is to find the ideology and goals to be conveyed by the advertiser through the language used. Norman Fairclough divides discourse analysis into three dimensions: text analysis, discussion practices, and sociocultural practices. In his model, the text is explained by looking at the structure of the text, such as understanding, sentences, and semantics. In addition, Fairclough's model analysis also pays attention to cohesiveness and coherence, namely the way words or sentences connect with each other to form meaning. Based on this research, it can be seen that the Pucuk Harum tea advertisement uses intelligent language and narrative to spread that the Pucuk Harum tea advertisement uses language understood by the community to spread certain ideologies and goals to the audience. Through a mature production strategy, the Pucuk Harum tea advertisement successfully conveys promotional messages effectively